THE KITCHEN IS IN THE LIVING ROOM: HOME DESIGN AND DECOR TV SHOWS AND LIFESTYLES AMONGST MIDDLE CLASSES IN SAO PAULO - Mira, Maria Celeste; Oliveira, Beatriz Salgado Cardoso de [UNESP] (Univ Fed Maranhao, Centro Ciencias Humanas, 2023)
In this paper we aim to better understand the propagation of new ways of living among the middle classes in Sao Paulo, more specifically, the trends known in the real estate market as American kitchen or gourmet kitchen and gourmet bal-cony . With reference to Pulici's (2011) ar-gument that the Sao Paulo elites do not li-ke this kind of kitchen's layout, and from the perception that the so-called open concept is a constant prescription in li-festyle media TV shows about home, reno-vation and design, we propose the hypo-thesis that it was aimed at some sector of the middle classes. We corroborate the ar-gument through various research techni-ques, as bibliographical research, syste-matic audience of TV shows that circulate worldwide on pay-TV channels, documen-tary research on architecture, real estate and tourism blogs, among others. In the end, it is suggested that the new concept of good living is related to a more general change, that encompasses other aspects of the middle classes' lifestyle, such as, for example, its entry into the world of gas-tronomy.
Keywords: Lifestyle media; Home and d?cor; Lifestyle; Middle class